Analisis Peningkatan Kinerja Siswa dalam Kerapihan Menjahit Kerah Jas Berbasis Metode Demonstrasi dan Eksperimen - Suryatin, Etin (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2012)
This study aims to find effective ways to teach using the demonstration and experimentation.The method used was action research with the research procedure is divided into two cycles.Each cycle begins with planning, action, observation and reflection.The instrument used in this study consists of three types of teacher observation, questionnaire responses of students and the work of the students.Analysis of the data processed by descriptive refers to the process and results of student work.The results showed that the use of demonstration and experimental methods can improve psychomotor skills, the use of blend and experimental demonstration method can increase the activity of students, and the use of demonstrations and experiments can be used by instructors as a teaching strategy.